2014
DOI: 10.1155/2014/609482
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Nanostructured TiCrN Films Prepared by DC Magnetron Cosputtering

Abstract: Nanostructured TiCrN films were grown on Si (100) wafers by reactive DC unbalanced magnetron cosputtering technique without external heating and voltage biasing to the substrates. The effects of Ti sputtering current on the chemical composition, chemical state, electronic structure, crystal structure, and morphology of the TiCrN films were characterized by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), atomic force microscopy (AFM), and field emission scanning electron microscopy (FE-SEM), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recent research found TiAlN with hardness values of up to 35GPa, which is 50% higher than that of TiN [6,7]. Further research investigated the influence of new dopants other than Al into the TiN lattice, such as: Si, Nb, Mo, B, Si and Cr amongst others [8][9][10][11][12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent research found TiAlN with hardness values of up to 35GPa, which is 50% higher than that of TiN [6,7]. Further research investigated the influence of new dopants other than Al into the TiN lattice, such as: Si, Nb, Mo, B, Si and Cr amongst others [8][9][10][11][12].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In all the films, it could be observed the chromium nitride Cr 2 N in the solid solution (Ti,Cr)N, whereas, the titanium nitride which coexists with Cr 2 N phase, evolves toward three phases: Ti 2 N, TiN 0.3 and TiN. This could be explained by the enthalpy formation of the nitride of Cr and Ti (ΔH TiN = − 337.65 kJ/mol and ΔH CrN = − 117.15 kJ/mol), which shows that the Ti-N is easier to be formed than Cr-N [32].…”
Section: Structure Analysesmentioning
confidence: 98%
“…Determining that the increase in the number of interfaces causes a distortion of the crystalline structure due to residual stresses within this multilayers system, which will influence the mechanical and tribological properties of this type of coatings. From these results it was possible to infer that all coatings have a face-centered cubic crystal structure (FCC) [5,10].…”
Section: Comparison Between Nitride Coatings 31 Structural Study For Tin and Ticrn Nitride Coatingsmentioning
confidence: 99%